A review of the genus Anthocomus Erichson, 1840 (Coleoptera, Cleroidea, Malachiidae) species of Inner Asia - Tshernyshev, Sergei E. (Zootaxa, 2021)
The distribution and species diversity of the genus Anthocomus Erichson, 1840 of Inner Asia are discussed. Nine species, Anthocomus (Celidus) equestris (Fabricius, 1781), Anthocomus (Anthocomus) abdominalis Pic, 1903, A.( A.) coreanus Pic, 1911, A. (A.) cyaneipennis Wittmer, 1940, A. (A.) limbellus (Wittmer, 1953), A. (A.) lineatipennis Wittmer, 1995, A. (A.) mongolicus Wittmer, 1969, A. (A.) similicornis Wittmer, 1999 and A. (A.) testaceoterminalis Wittmer, 1995 known from the region and adjacent territories are reviewed. The placement of four species, ? A. (A.) coreanus Pic, 1911, ? A. (A.) cyaneipennis Wittmer, 1940, ? A. (A.) limbellus (Wittmer, 1953) and ? A. (A.) mongolicus Wittmer, 1969 in the genus Anthocomus Erichson is discussed as doubtful. A new species, Anthocomus (Anthocomus) kovali Tshernyshev, sp. n. from Wexi mountains, Yunnan Province, China is described and illustrated. The new species differs in its monochromous orange-yellow elytra with orange-red apical impressions yellow within, appendages orange-brown, head, pronotum, scutellum and palpi dark brown to black and lacking metallic luster, antennae dark brown.